American medicine, the quest for competence - Good, Mary-Jo DelVecchio (University of California Press, 1995)
What does it mean to be a good doctor in America today? How do such challenges as new biotechnologies, the threat of malpractice suits, and proposed health-care reform affect physicians' ability to provide quality care? These and many other crucial questions are examined in this book.